2005
DOI: 10.1007/s10562-004-3458-1
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective asymmetry transfer hydrogenation of prochiral acetophenone catalyzed by palladium?chitosan on silica

Abstract: The chitosan-palladium catalyst supported on silica was prepared and used to catalyze an asymmetry transfer hydrogenation of prochiral acetophenone to alcohol with formate salts as a hydrogen donor at atmosphere. The results indicate that palladium coordinates with amino group in chitosan to form palladium-chitosan complex and its performance for an asymmetry transfer hydrogenation of acetophenone is affected greatly by the reaction temperature, hydrogen donor and solvent. For the hydrogenation of acetophenone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…As showed in Table 2, there is no reaction took place in the absence of catalyst or in the presence of CS-Pd. After 3 h hydrogenation, SiO 2 -CS-Pd exhibited activity of hydrogenation but only 1-tetrahydronaphthalenol was formed as the sole product, which was accordance with reported results that silica supported CS-Pd catalyst has catalytic activity for hydrogenation of ketones to form corresponding alcohols [19,20]. Yuan [19] once reported that the asymmetry transfer hydrogenation of acetophenone catalyzed by silica supported CS-Pd catalyst, and an optical yield of R-1-phenylethanol could reach 99% after 8 h reaction at 303 K under atmosphere hydrogen.…”
Section: Catalytic Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…As showed in Table 2, there is no reaction took place in the absence of catalyst or in the presence of CS-Pd. After 3 h hydrogenation, SiO 2 -CS-Pd exhibited activity of hydrogenation but only 1-tetrahydronaphthalenol was formed as the sole product, which was accordance with reported results that silica supported CS-Pd catalyst has catalytic activity for hydrogenation of ketones to form corresponding alcohols [19,20]. Yuan [19] once reported that the asymmetry transfer hydrogenation of acetophenone catalyzed by silica supported CS-Pd catalyst, and an optical yield of R-1-phenylethanol could reach 99% after 8 h reaction at 303 K under atmosphere hydrogen.…”
Section: Catalytic Activitysupporting
confidence: 92%
“…More recently, with the development of environmentally friendly industries, CS-supported metals catalysts have attracted a lot of attention because CS shows these advantages of nontoxicity and desirable physical and mechanical properties [10][11][12][13]. In previous papers [14][15][16][17][18], a silica-supported CS-palladium complex abbreviated as SiO-CS-Pd has been found to catalyze the hydrogenation of nitrotoluene, nitrobenzene, chlorophenol, 2-octene and 3-octene, et al Some ketones can reduce to chiral alcohols catalyzed by silica supported CS-Pd complex via asymmetric hydrogenation [19,20]. However, the successful application of CS stabilized palladium catalysts in hydrogenolysis reactions of C=O to CH 2 groups has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…At 80 °C, an enantiomeric excess of R ‐1‐phenylethanol reaches 68 % in the optimized conditions. The simple preparation, easy handling and usage in atmosphere are the striking features of the catalyst . Even the non‐noble metal complexes were used for such hydrogenations.…”
Section: N‐containing Biopolymers As An Efficient Catalystmentioning
confidence: 99%
“…The simple preparation, easy handling and usage in atmosphere are the striking features of the catalyst. [104] Even the non-noble metal complexes were used for such hydrogenations. Silica supported chitosan-cobalt complexes were found to be a high stereo selective catalyst for asymmetric hydration of 1-octene (Scheme 11.6).…”
Section: Hydrogenation Reactionsmentioning
confidence: 99%
“…[163] Given the chiral character of the chitosan support, it seems worthwhile to address the effect of the underlying chiral support upon the enantioselectivity of asymmetric reactions. Silica-chitosan hybrids containing Pd, [171] Fe and/or Ni ions [172] were used in asymmetric hydrogenations, yielding average to excellent enantioselectivities. As the attached groups were not chiral, the chiral induction should stem from the close proximity of the underlying chiral backbone of the chitosan polymer.…”
Section: Catalyst Immobilisation On the Bio-polymer Chitosanmentioning
confidence: 99%